2013
DOI: 10.3109/17435390.2013.796534
|View full text |Cite
|
Sign up to set email alerts
|

Principal component and causal analysis of structural and acutein vitrotoxicity data for nanoparticles

Abstract: Structure toxicity relationship analysis was conducted using principal component analysis (PCA) for a panel of nanoparticles that included dry powders of oxides of titanium, zinc, cerium and silicon, dry powders of silvers, suspensions of polystyrene latex beads, and dry particles of carbon black, nanotubes and fullerene, as well as diesel exhaust particles. Acute in vitro toxicity was assessed by different measures of cell viability, apoptosis and necrosis, haemolytic effects and the impact on cell morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 44 publications
4
37
0
1
Order By: Relevance
“…It should be mentioned here that, as the toxicity is highly dose-dependent, the toxicological effects are usually evaluated at multiple concentrations in a series of tests the results of which are represented with a doseresponse curve. Figure 6 shows an example of dose-response curves obtained for 18 NPs (Xue Zhong Wang, et al, 2014). As can be seen from this graph, the cell viability is lower in the cells treated with N3 (nanotubes), N14 (zinc oxide) and N6 (aminated beads).…”
Section: Nano-(q)sar Researchmentioning
confidence: 94%
See 1 more Smart Citation
“…It should be mentioned here that, as the toxicity is highly dose-dependent, the toxicological effects are usually evaluated at multiple concentrations in a series of tests the results of which are represented with a doseresponse curve. Figure 6 shows an example of dose-response curves obtained for 18 NPs (Xue Zhong Wang, et al, 2014). As can be seen from this graph, the cell viability is lower in the cells treated with N3 (nanotubes), N14 (zinc oxide) and N6 (aminated beads).…”
Section: Nano-(q)sar Researchmentioning
confidence: 94%
“…There are different methods to analyse and compare dose response curves such as area under the curve, slope of the curve, threshold values, min/max response and benchmark dose approach. In this study, (Xue Zhong Wang, et al, 2014) performed PCA in order to integrate the entire curve and used the resulting principal components as an overall measure of cumulative response. They concluded that, compared to other approaches, PCA-based representation of the dose-response curves provides more reasonable results when ranking the ENMs according to their hazard potential.…”
Section: Nano-(q)sar Researchmentioning
confidence: 99%
“…Despite these limitations, there is a growing literature on the use of (Q)SARlike models in nanotoxicology studies. There are a great number of reviews [3,5,10,[12][13][14] and research articles [15][16][17][18][19][20][21][22][23][24][25][26][27][28] devoted to the investigations of in silico modelling of ENM toxicity in peer-reviewed scientific journals.…”
Section: "[Insert Figure 1 About Here]"mentioning
confidence: 99%
“…The research conducted by Wang et al [23] has been revealed to be one of the most useful datasets for nano-(Q)SAR modelling. The authors selected a panel of 18 ENMs with varying structures and conducted a set of in vitro cytotoxicity assays, including LDH release, apoptosis, necrosis, viability, MTT and haemolytic effects.…”
Section:  Sample Sizementioning
confidence: 99%
See 1 more Smart Citation